102 - ALIMENTARY HABITS AND HYDRATION PRÉ-, DURING AND POST-TRAINING AN ON UNIVERSITY FEMALE FUTSAL TEAM, RIO DE JANEIRO (Fiep Bulletin - online, 2011)
In all sporting modality, among them Futsal, is indispensable that the contribution of nutrients assists each athlete's individual needs, seeking to optimize the allied physical income to the program of exercises. The present study describes the dietary habits and hydration in the pre-, during and post-training on an university women's Futsal team, Rio de Janeiro. In September 2008, it was realized a descriptive, cross-sectional and with primary base study with ten female athletes, aged from 19 to 28 years old, volunteers, all belonging to futsal female team from UNISUAM. A formulary was developed to make athlete's nutritional follow-up, and it was used by students of nutrition both pré-, during and post-training. Data were typed, consolidated and analyzed by the software Excel for Windows 2007, as well as explored by means of absolute and relative frequencies and measures of central tendency (average and standard deviation) from the selected variables. The athletes' average age (years) was 22.9±1.6; average height (m) was 1.65±0.07; and average body weight (Kg) were 62.4±8.3Kg. As for the meal type, it was verified that all have a snack before the training. Among athletes, 36.4% used to hydrate themselves before physical training; 100% ingest liquid drinks during training, and 90.9% hydrate themselves after training, however the amount (ml) was insufficient. The conclusion is that the athletes don't feed and do not hydrate themselves appropriately before training.
Keywords: Alimentary Habits; Futsal; Hydration